Persepsi Karyawan Bank Pemerintah Di Kota Batam Tentang Internal Audit - Natalia, Erni Yanti; Wasiman, Wasiman; Sitorus, David Humala (LPPM Universitas Putera Batam, 2024)
Corruption, Asset Misuse and Financial Statement Fraud are three types of fraud that often occur in financial and business contexts. The forerunner of opportunities to commit fraud is one of the reasons for the weakness of Internal Audit in a company. This study aims to find out how the perception of government bank employees in Batam City about the Internal Audit is carried out. The qualitative descriptive research method is by collecting data in the form of a questionnaire using indicators presented by The Institute of Internal Auditors. The collected data is then processed and interpreted and conclusions are drawn using the level of perception, namely: Negative if the average percentage of total component items ≤ 40%, and Positive if the average percentage of total component items > 40%. The results of the study showed: (1) The perception of Government bank employees (BUMN) for the indicators of Manage Internal Audit Activities, The Nature Of Work, Assignment Planning, Implementation Of Assignments, Communication Of Assignment Results, Monitoring Progress, Communication On Risk Acceptance showed positive results because the percentage of respondents who answered Agree and Strongly Agree > 40%.; (2) There is a perception of Government bank employees who show Negative by answering Disagree, namely for The Nature Of The Work indicator, statement item number 4, which is 1.3% and for statement indicator number 9 as much as 1.3% as well. However, this result is < 40% so it can be said that it is not significant indicating a negative result.